2000
DOI: 10.2460/ajvr.2000.61.1322
|View full text |Cite
|
Sign up to set email alerts
|

Activities of NADPH-dependent reductases and sorbitol dehydrogenase in canine and feline lenses

Abstract: Results indicate that during periods of hyperglycemia, sorbitol would accumulate at a faster rate in the lenses of cats than in the lenses of dogs. Thus, the higher incidence of diabetic cataracts in dogs, compared with cats, is likely not attributable to a difference in the ratio of NADPH-dependent reductases activity-to-sorbitol dehydrogenase activity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
3
0
3

Year Published

2002
2002
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 13 publications
0
3
0
3
Order By: Relevance
“…All these enzymes are distinguished by their ability to reverse oxidative damage and stress. NADPH dehydrogenase transforms enzymes and proteins back into their reduced state by the exchange of electrons between NADPH and NADP [11] . HO-1 may be involved indirectly in the antioxidant system by converting heme to other products such as iron (II), carbon monoxide, and biliverdin [12] .…”
Section: Introductionmentioning
confidence: 99%
“…All these enzymes are distinguished by their ability to reverse oxidative damage and stress. NADPH dehydrogenase transforms enzymes and proteins back into their reduced state by the exchange of electrons between NADPH and NADP [11] . HO-1 may be involved indirectly in the antioxidant system by converting heme to other products such as iron (II), carbon monoxide, and biliverdin [12] .…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, research from the Zurich group comparing the ratios of NADPH reductases and sorbitol dehydrogenase in the dog and cat lens suggested that sorbitol would accumulate at a faster rate in the cat than the dog lens; the difference in diabetic cataractogenesis between the two species cannot be explained by differences in enzyme ratio. 22 Further work from the same group working under Professor Bernard Speiss demonstrated posterior cortical opacities in feline lenses cultured in high glucose concentrations though these occurred in young but not old cats. 23 In that study canine lenses developed equatorial vacuoles but not the characteristic mature cataract seen in 80% of dogs within 16 months of diagnosis in one recent study.…”
Section: Discussionmentioning
confidence: 99%
“…Other biochemical processes such as protein glycation and the formation of advanced glycation end products (AGEs) through the Maillard reaction are considered important in human diabetic cataractogenesis, 20,21 and may also occur in the cat. Indeed, research from the Zurich group comparing the ratios of NADPH reductases and sorbitol dehydrogenase in the dog and cat lens suggested that sorbitol would accumulate at a faster rate in the cat than the dog lens; the difference in diabetic cataractogenesis between the two species cannot be explained by differences in enzyme ratio 22 . Further work from the same group working under Professor Bernard Speiss demonstrated posterior cortical opacities in feline lenses cultured in high glucose concentrations though these occurred in young but not old cats 23 .…”
Section: Discussionmentioning
confidence: 99%
“…Одним з шляхів утилізації глюкози за цукрового діабету є поліольний метаболічний шлях, який включає дві основні біохімічні реакції: відновлення глюкози до шестиатомного спирту сорбітолу та перетворення останнього у фруктозу під дією ферменту сорбітолдегідрогенази (СДГ) (Jeffery & Jörnvall, 1983;Liang-jun, 2018). Фермент СДГ запобігає накопиченню сорбітолу, який, локалізуючись у кришталиках ока, спричиняє виникнення діабетичної катаракти, у клітинах інших тканин збільшує осмолярність (De Leeuw et al, 1993;Salgado et al, 2000).…”
Section: вступunclassified
“…Експериментальні дослідження показали, що введення інгібітора СДГ призводить до виникнення нейропатій (Schmidt et al, 2001) 2000), разом з тим, за даними зарубіжних вчених активність даного ферменту у людей з цукровим діабетом достовірно не відрізнялася від здорових. Такі відмінності, можливо, обумовлені видовими особливостями поліолового шляху обміну глюкози (De Leeuw et al, 1993;Salgado et al, 2000). Установлено, що у кришталиках ока котів спирт сорбітол накопичується інтенсивніше, ніж у собак, однак частота діабетичної катаракти вища саме у собак (Salgado et al, 2000).…”
Section: вступunclassified